Extracting Genomic DNA of Fossilised Pollens from Volcanic Soil Sediment of Liyangan Site-Central Java. Issue 1 (November 2020) - Sasongko, ND; Windriyani,; Siswanto,; Aziz, S
Abstract: Liyangan buries some artifacts in volcanic sediment, including pollens. Reconstructing ancient plant diversity requires good quality in an adequate amount of genomic DNA from fossilized pollen. The current study was aimed to separate pollens from their sediment and extract the pollens. The separation was done according to different protocols (BALAR's and Geology's), DNAs were extracted by applying modified-CTAB and mini Genomic DNA Mini Kit . Current data showed the two separation and extraction protocols were able to separate fossilized pollens and so to extract them. The BALAR method combined with CTAB resulted in 314µg/ml to 887µg/ml while a lower amount of 382µg/ml to 852µg/ml were obtained when extracted by DNA Mini Kit . The Geology protocol combined with CTAB resulted in even lower concentrations (43µg/ml to 230µg/ml); and 22 µg/ml to 216 µg/ml by DNA Mini Kit . The BALAR's protocol performed a better result in separating fossilized pollens from other materials. Both extraction methods resulted in an adequate amount of genomic DNA, although in quite low quality.